Strategi Kebijakan Stabilisasi Harga Komoditas Pangan di Provinsi Sumatera Utara - Rasidin Karo Karo Sitepu; Mhd Asaad; Veralianta Br Sebayang (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
Food commodities are included in the volatile food category which is dominant in determininginflation because prices fluctuate so that they contribute to national and regional inflation. Thisstudy aims to analyze price stabilization and formulate policy recommendations to anticipatestrategic food commodity price fluctuations in North Sumatra province. Using weekly secondarydata, for the period January 2021-December 2022 (104 observations). Technical analysis using theARIMA model and the Coefficient of Variation. The results of the analysis with reference to pricestabilization indicators as a reference in stabilizing food supply and prices at the consumer levelindicate that there are seven commodities that need immediate intervention, namely Dry SeedSoybeans, Cooking Oil, Chicken Eggs, Pure Beef, Wheat Flour and Sugar. Sand. Alternative policiesin order to maintain the stability of food prices are (1) affordable prices, (2) availability of supplies,(3) smooth distribution and, (4) effective communication. These four strategies can be implementedin the form of (1) carrying out low-cost food market operations, (2) monitoring prices and dailysupplies carried out by the Food Officers Unit, (3) conducting food commodity bazaars before andduring the HBKN, (4) inter-governmental cooperation. Regional, (5) Efforts to provide food commodity supplies, (6) Active distribution of commodities to several markets in the North Sumatraregion, (7) Intensive coordination with TPID with the Ministry of Trade and the Economic Bureau ofthe North Sumatra Provincial Government, (8) High Level implementation TPID meetings ahead ofand during HBKN in several districts/cities of North Sumatra province, and (9) Use of RegionalIncentive Funds to increase food availability.Keywords: ARIMA, price fluctuation, coefficient of variation, price stabilization